Measurement of the tt[bar] production cross-section and lepton differential distributions in eμ dilepton events from pp collisions at √s=13TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Helary, Louis; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; Mkrtchyan, Tigran; Napolitano, Fabrizio; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2020)
The inclusive top quark pair (tt̄) production cross-section σtt̄ has been measured in proton–proton collisions at s√=13TeV, using 36.1 fb−1 of data collected in 2015–2016 by the ATLAS experiment at the LHC. Using events with an opposite-charge eμ pair and b-tagged jets, the cross-section is measured to be: σtt¯=826.4±3.6(stat) ±11.5(syst) ±15.7(lumi) ±1.9(beam)pb, where the uncertainties reflect the limited size of the data sample, experimental and theoretical systematic effects, the integrated luminosity, and the LHC beam energy, giving a total uncertainty of 2.4%. The result is consistent with theoretical QCD calculations at next-to-next-to-leading order. It is used to determine the top quark pole mass via the dependence of the predicted cross-section on mpolet, giving mpolet=173.1+2.0−2.1GeV. It is also combined with measurements at s√=7TeV and s√=8TeV to derive ratios and double ratios of tt¯ and Z cross-sections at different energies. The same event sample is used to measure absolute and normalised differential cross-sections as functions of single-lepton and dilepton kinematic variables, and the results are compared with predictions from various Monte Carlo event generators.
ATLAS Collaboration: G. Aad, V. Andrei, A.E. Bolz, M. Dunford, S. Franchino, L. Helary, M. Klassen, A. Krishnan, A. Kugel, T. Mkrtchyan, F. Napolitano, P.S. Ott, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und 2933 weitere]
Im Titel steht der zweite Buchstabe t mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 08.10.2020